2006
DOI: 10.1002/dvdy.20704
|View full text |Cite
|
Sign up to set email alerts
|

Genes, forces, and forms: Mechanical aspects of prenatal craniofacial development

Abstract: Current knowledge of molecular signaling during craniofacial development is advancing rapidly. We know that cells can respond to mechanical stimuli by biochemical signaling. Thus, the link between mechanical stimuli and gene expression has become a new and important area of the morphological sciences. This field of research seems to be a revival of the old approach of developmental mechanics, which goes back to the embryologists His (1874), Carey (1920), and Blechschmidt (1948). These researchers argued that f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 68 publications
0
18
0
1
Order By: Relevance
“…More importantly, Sinsel et al(1998;1999) revealed that paralysis of the midfacial musculature can result in decreased anterioposterior growth of the snout and nasofrontal sutural growth activity. Actually, mechanical forces play a fundamental role in tissue differentiation and morphogenesis (Radlanski and Renz, 2006). The findings from this study (Figs.3 and 4) show that perioral forces exerted on the primary dentition of class III malocclusion were apparently less than the normal (P<0.01), especially for the upper anterior teeth region with negligible pressure which may cause less bone apposition in this area.…”
Section: Possible Relationships Between Class III Malocclusion and Pementioning
confidence: 55%
“…More importantly, Sinsel et al(1998;1999) revealed that paralysis of the midfacial musculature can result in decreased anterioposterior growth of the snout and nasofrontal sutural growth activity. Actually, mechanical forces play a fundamental role in tissue differentiation and morphogenesis (Radlanski and Renz, 2006). The findings from this study (Figs.3 and 4) show that perioral forces exerted on the primary dentition of class III malocclusion were apparently less than the normal (P<0.01), especially for the upper anterior teeth region with negligible pressure which may cause less bone apposition in this area.…”
Section: Possible Relationships Between Class III Malocclusion and Pementioning
confidence: 55%
“…Past work has found the critical period of TMJ morphogenesis to coincide with the onset of buccal, or mouth, cavity motion during embryogenesis [42]. Others have identified the link between molecular signaling and mechanical stimulation to be fundamental to the development of the fetal mandible and overall craniofacial growth [43]. This suggests that a similar interplay between stimuli is likewise essential for development of the TMJ.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on animal models and human genetic disorders have led to increased knowledge about the processes of craniofacial morphogenesis and genes related to these processes (Wilkie and Morriss-Kay, 2001;Cohen, 2002;Kuratani, 2005;Radlanski and Renz, 2006). However, the common genetic factors that explain facial variation among human individuals or facial difference among populations remain unclear.…”
Section: Genetic and Environmental Factorsmentioning
confidence: 99%